1993
DOI: 10.1289/ehp.93101s353
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenicity and human chromosomal effect of stevioside, a sweetener from Stevia rebaudiana Bertoni.

Abstract: Leaves of Stevia rebaudiana Bertoni have been popularly used as a sweetener in foods and beverages for diabetics and obese people due to their potent sweetener stevioside. In this report, stevioside and steviol were tested for mutagenicity in Salmonella typhimurium strains TA98 and TA100 and for chromosomal effects on cultured human lymphocytes. Stevioside was not mutagenic at concentrations up to 25 mg/plate, but showed direct mutagenicity to only TA98 at 50 mg/plate. However, steviol did not exhibit mutageni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 6 publications
0
10
0
2
Order By: Relevance
“…Although some work has failed to demonstrate carcinogenic, teratogenic, mutagenic or toxic actions of stevioside (78), after oral administration to rats [108][109][110][111], at doses up to 1.2 % of the diet, and considering, therefore, a maximum ingestion recommendable of 7.94 mg·kg -1 ·d -1 for the human organism [112], others have demonstrated that steviol (24), an aglycone obtained from complete hydrolysis of stevioside, showed a high toxicity in pregnant females and embryos of hamsters, at doses of 0.75 and 1.00 mg·kg -1 ·d -1 , administered from 6 th to 10 th day of gestation [112][113][114]. The animals treated with these doses showed acute renal failure, embryotoxic effects such as weight loss and retardation of the process of fetal ossification, and death.…”
Section: R' = R" = Hmentioning
confidence: 99%
“…Although some work has failed to demonstrate carcinogenic, teratogenic, mutagenic or toxic actions of stevioside (78), after oral administration to rats [108][109][110][111], at doses up to 1.2 % of the diet, and considering, therefore, a maximum ingestion recommendable of 7.94 mg·kg -1 ·d -1 for the human organism [112], others have demonstrated that steviol (24), an aglycone obtained from complete hydrolysis of stevioside, showed a high toxicity in pregnant females and embryos of hamsters, at doses of 0.75 and 1.00 mg·kg -1 ·d -1 , administered from 6 th to 10 th day of gestation [112][113][114]. The animals treated with these doses showed acute renal failure, embryotoxic effects such as weight loss and retardation of the process of fetal ossification, and death.…”
Section: R' = R" = Hmentioning
confidence: 99%
“…The economic importance of stevioside (78), derived from its great world-wide consumption, has motivated diverse work aiming to characterize and establish the safe levels of this kaurane glycoside and its metabolites in the human organism [106,107]. Although some work has failed to demonstrate carcinogenic, teratogenic, mutagenic or toxic actions of stevioside (78), after oral administration to rats [108][109][110][111], at doses up to 1.2 % of the diet, and considering, therefore, a maximum ingestion recommendable of 7.94 mg•kg -1 •d -1 for the human organism [112], others have demonstrated that steviol (24), an aglycone obtained from complete hydrolysis of stevioside, showed a high toxicity in pregnant females and embryos of hamsters, at doses of 0.75 and 1.00 mg•kg -1 •d -1 , administered from 6 th to 10 th day of gestation [112][113][114]. The animals treated with these doses showed acute renal failure, embryotoxic effects such as weight loss and retardation of the process of fetal ossification, and death.…”
Section: R' = R" = Hmentioning
confidence: 99%
“…Briefly, pharmacological activities and therapeutical benefits include antitumour and anticancer, antiinflammatory, antihyperglycemic, antihypertensive, antidiarrheal, immunomodulatory, diuretic, and enzyme inhibitory actions. Stevia has also been used to help control weight in obese subjects [14]; moreover, antioxidant properties have been described [15, 16]. Stevioside, rebaudioside A, and their metabolite steviol have been mostly investigated in in vivo animal studies and, at a lesser extent, in humans.…”
Section: Introductionmentioning
confidence: 99%